Українська мова у професійному спілкуванні: комунікація майбутніх ІТ-фахівців - Шарова, Тетяна Михайлівна; Шарова, Татьяна Михайловна; Sharova, Tetiana (My University, 2021)
UK: У статті акцентується увага на професійному спілкування майбутніх ІТ-фахівців. Наголошено на тому, що нині навіть на побутовому рівні користувачі персональних комп’ютерів, ноутбуків використовують спеціальну термінологію, а іноді специфічний сленг, який свідчить про своє діне мовлення майбутніх ІТ-фахівців. Останнім часом з’являється багато сучасних словників, у тому числі створюються словники програмістів, де вказані не лише терміни, а й тлумачення нових слів, іноді поєднання українських та англійських словоутворень. У дослідженні вказано на те, що термінологія ІТ-фахівців досить часто дублює комп’ютерний сленг. Це пояснюється відсутністю власного позначення термінів, які використовуються під час комунікації програмістів чи ІТ-фахівців. EN: The article focuses on the professional communication of future IT professionals. It is emphasized that today, even at the household level, users of personal computers and laptops use special terminology, and sometimes specific slang, which testifies to the current speech of future IT professionals. Recently, many modern dictionaries have appeared, including dictionaries of programmers, which indicate not only terms but also interpretations of new words, sometimes a combination of Ukrainian and English word formations. The article provides examples of word terms, as well as a tabular version of the translation of words from English and the interpretation of computer terms. The most popular or most commonly used terms and concepts understood by a beginner PC were taken into account. The scientific publication reveals the peculiarities of using dictionaries for online programmers. It is pointed out that recently in the Internet space you can find links to electronic resources, which contain terms that can be used in professional communication by IT professionals. The study found that IT terminology often duplicates computer slang. This is due to the lack of self-designation of terms used in the communication of programmers or IT professionals. The study points to certain words (slang), which are most often borrowed from English. Such terms are not even translated into Ukrainian. They usually need to be memorized and used in the professional activities of a person working with information technology.
Ukrainian language in professional communication: communication of future it professional
Keywords: комунікація; сленг; професійна лексика; словник програміста; communication; slang; professional vocabulary; programmer's dictionary